RIP Kinases in Liver Cell Death, Inflammation and Cancer. Issue 1 (January 2019) - Kondylis, Vangelis; Pasparakis, Manolis
Abstract : Cell death is intrinsically linked to inflammatory liver disease and cancer development. Recent genetic studies have suggested that receptor-interacting protein kinase (RIPK)1 is implicated in liver disease pathogenesis by regulating caspase-dependent hepatocyte apoptosis induced by tumor necrosis factor (TNF) or other stimuli. In contrast, the contribution of caspase-independent RIPK3/mixed lineage kinase like (MLKL)-mediated hepatocyte necroptosis remains debatable. Hepatocyte apoptosis depends on the balance between RIPK1 prosurvival scaffolding functions and its kinase-activity-mediated proapoptotic function. Several regulatory steps promote the prosurvival role of RIPK1, including phosphorylation and ubiquitination of RIPK1 itself and other molecules involved in RIPK1 signaling. Pharmacological inhibition of liver damage by targeting RIPK1 signaling emerges as a potential therapeutic strategy to prevent chronic liver inflammation and hepatocarcinogenesis. Highlights: Hepatocyte apoptosis has long been observed in inflammatory liver diseases, but its pivotal role in driving chronic hepatitis and liver cancer has only recently been established. RIPK1 has emerged as a key determinant of cell survival or death through its scaffolding properties or its kinase activity. The interplay of RIPK1 with the IKK complex, TAK1, TRAF2, and cIAPs regulates NF-κB-dependent and independent cell survival mechanisms at transcriptional and post-translational levels. The relevance of RIPK1/RIPK3-mediated hepatocyte necroptosis for liver disease pathogenesis is debated, while RIPK3 functions in immune or other non-hepatocyte liver cell types have been suggested. Pan-caspase inhibitors are currently in clinical trials for liver disease patients and genetic data suggest that RIPK1 inhibitors may also prevent liver damage without serious side effects.